2014
DOI: 10.18632/oncotarget.2157
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-101 targets EZH2, MCL-1 and FOS to suppress proliferation, invasion and stem cell-like phenotype of aggressive endometrial cancer cells

Abstract: MicroRNA-101 has been implicated as a tumor suppressor miRNA in human tumors. However, its potential functional impact and the underlying mechanisms in endometrial cancer progression have not been determined. Here, we report that in aggressive endometrial cancer cells, re-expression of microRNA-101 leads to inhibition of cell proliferation and induction of apoptosis and senescence. Ectopic overexpression of microRNA-101 attenuates the epithelial-mesenchymal transition-associated cancer cell migration and invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
130
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(133 citation statements)
references
References 58 publications
3
130
0
Order By: Relevance
“…In aggressive endometrial cancer cells, re-expression of miR-101 leads to inhibition of cell proliferation and induction of apoptosis and senescence [22]. In human diploid fibroblasts (HDFs), miR-141 induces premature senescence via posttranscriptionally downregulating BMI1.…”
Section: Discussionmentioning
confidence: 99%
“…In aggressive endometrial cancer cells, re-expression of miR-101 leads to inhibition of cell proliferation and induction of apoptosis and senescence [22]. In human diploid fibroblasts (HDFs), miR-141 induces premature senescence via posttranscriptionally downregulating BMI1.…”
Section: Discussionmentioning
confidence: 99%
“…miR-101 was found to suppress the EMT and CSC properties of aggressive EC cells at least in part by attenuating EZH2 expression, followed by elevation of BAX, p21, epithelial markers and TIMP3, downregulation of mesenchymal markers and suppression of Wnt/ B-catenin pathway (Konno et al 2014). A recent study suggested oncogenic role for hsa-miR-181a in endometrial tumorigenesis and its critical role in tumor metastasis of advanced EC (He et al 2015).…”
Section: Role Of Epigenetic Modifications and Mirna Regulationmentioning
confidence: 97%
“…Micro-RNA also seems to have a role on EMT, namely micro-RNA-194 that suppresses the gene BMI-1 in endometrial cell lines, involved in EMT and possibly also on metastasis process [60]. The overexpression of micro-RNA 101 was linked to stem cell-like properties, including EMT, cell migration, inhibited tumorosphere capacity and chemosensitivity to paclitaxel in human serous endometrial cancer cell line [73]. A transcriptional factor important for self-renewal capacity and undifferentiated state of embryonic stem cells is SALL4 that was already described in endometrial cancer [74].…”
Section: Endometrial Cancer Stem Cellsmentioning
confidence: 98%